Didelphis albiventris as a carrier of Leptospira sp. in the central nervous tissue in the semiarid region of Northeast, Brazil - Fernandes, Juciê Jales; de Lima Peixoto, Aline; de Farias, Alick Sulliman Santos; Junior Pinheiro, Tiago; da Costa, Diego Figueiredo; Silva, Maria Luana Cristiny Rodrigues; Júnior, João Pessoa Araújo [UNESP]; Malossi, Camila Dantas [UNESP]; Ullmann, Leila Sabrina [UNESP]; de Azevedo, Sergio Santos; Alves, Clebert José; dos Santos Higino, Severino Silvano (Elsevier, 2020)
Leptospirosis has been investigated in several species of wild animals. The white-eared opossum (Didelphis albiventris) is a mammal common in the brazilian semi-arid, so, this study aimed to investigate its role in the occurrence of the leptospirosis in the region Northeast of Brazil. 12 animals were used, from which samples were collected for the attempt of isolation, molecular detection and serological examination. There was no microbial growth, nor were any anti-Leptospira sp. antibodies found in the serological samples. The PCR detected leptospiric DNA in the central nervous system (CNS) of five animals (41.7 %). The gene in one of the samples was sequenced and showed identity with Leptospira interrogans. The presence of Leptospira sp. in the CNS of Didelphis albiventris does not allow the characterization of the studied animals as reservoirs with potential for transmission of the pathogen in the region, however it represents a site that needs to be further investigated.
Keywords: Leptospirosis; Nervous tissue; Opossum; Reservoirs